The creative tarot eaudiobook A modern guide to an inspired life. - Crispin, Jessa (Tantor Media, 2020)
A hip, accessible, and practical guide for artists and creative people looking to tarot for guidance and inspiration in the tradition of The Secret Language of Birthdays and Steal Like an Artist . What if the path to creativity was not as challenging as everyone thinks? What if you could find that spark, plot twist, or next project by simply looking at your life and your art through a different lens? Written for novices and seasoned readers alike, The Creative Tarot is a unique guidebook that reimagines tarot cards and the ways they can boost the creative process. Jessa Crispin guides you through the intuitive world of the tarot to get those creative juices flowing again. Thought to be esoteric and mystical, tarot cards are approachable and endlessly helpful to overcoming creative blocks. Crispin offers spiritual readings of the cards, practical information for the uninspired artist, and a wealth of fascinating anecdotes about famous artists including Virginia Woolf, Rembrandt, and David Bowie, and how they found inspiration.